Pengembangan Pengembangan Sistem Peminjaman Barang Berbasis Online Pada Sistem Pengelolaan Aset FTI UKSW - BIllstein Maelgweyn Lelatobur Maelgwyn Lelatobur (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The process of borrowing assets for the academic community is generally carried out on a regular basis. However, in the process of borrowing assets, there are times when laboratory officers have difficulty when borrowing because many laboratory officers have to check the conditions one by one manually. With these problems, this research will design and build an online-based goods lending system that can make it easier for laboratory workers to manage asset data.